Conditions effecting the mortality of chicks - Philips, Allen G. (My University, 1907)
Introduction: At the present day one of the greatest problems confronting the old and especially the new breeder of poultry is the reason for the death of so many of our newly hatched chicks. In order for a breeder to successfully raise young poultry, he should in some measure be able to answer this question. To get.at the bottom of this problem we should begin with the parent stock. In the first place the parents should be strong, healthy and vigorous, and if possible allowed plenty of range. Food that is nitrogenous should predominate in the feeding, and the ratio of carbohydrates to proteids should be as 1 to 4. The exercise and green food problem can be solved by allowing plenty of range and pasture. It has been shown conclusively at the station here, that hens kept in small pens and not furnished with sufficient green or succulent food will not produce strong fertile eggs. If the eggs which are set with the intention of obtaining good chicks, are not strong and fertile to begin with, our success is doubtful. After securing the proper basis for the production of our young poultry we must look to our means of incubation. It is a conceded fact that where poultry is to be raised in any number, incubators have by far the preference. The kind of incubator to be used for hatching chicks something no one can tell, but from all indications shown here in the comparative uses of different incubators, the hot water machine has the preference. We cannot go into detail and tell just why this seems to be so, for that would involve an experiment along another line.
Citation: Philips, Allen G. Conditions effecting the mortality of chicks. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Poultry; Chick Mortality; Conditions Affecting Chicken Growth; Chicken Health; Theses